2005
DOI: 10.2298/bah0506093m
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile of milk from sheep raised on mountain pastures

Abstract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… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…The content of C16:0 in analyzed samples of milk from the Livno area was opposite to the samples from the Travnik area. The content of C16:0 in milk samples from the Livno area was higher in the I sampling period but without statistically significant difference compared to the II period (August), which is consistent with the results of the research (Mihaylova et al, 2005) who point out that the content of C16:0 and C18:0 was the highest in sheep's milk in July. The content of C16:0 in analyzed milk samples from the Travnik area grew by sampling periods and a statistically significant value in comparison to the previous two sampling was recorded in September Table 2.…”
Section: Resultssupporting
confidence: 90%
“…The content of C16:0 in analyzed samples of milk from the Livno area was opposite to the samples from the Travnik area. The content of C16:0 in milk samples from the Livno area was higher in the I sampling period but without statistically significant difference compared to the II period (August), which is consistent with the results of the research (Mihaylova et al, 2005) who point out that the content of C16:0 and C18:0 was the highest in sheep's milk in July. The content of C16:0 in analyzed milk samples from the Travnik area grew by sampling periods and a statistically significant value in comparison to the previous two sampling was recorded in September Table 2.…”
Section: Resultssupporting
confidence: 90%
“…MUFA and PUFA concentrations decreasing across lactation has been reported by Mihaylova et al . (2005) and our data agree with this, in contrast to the increase reported by Meľuchová et al . (2008) or lack of consistent variation reported by Salari et al .…”
Section: Discussionsupporting
confidence: 84%
“…We observed higher PUFA and MUFA percentage than earlier reports for sheep milk (Markiewicz-Kęszycka et al, 2013; Aguilar et al, 2014, both unspecified breed), sheep milk of Improved Wallachian, Tsigai, Lacaune sheep, and their crossbreds kept under different feeding regimes (Ostrovský et al, 2009) or sheep milk from Spanish genetic resources (Signorelli et al, 2008). MUFA and PUFA concentrations decreasing across lactation has been reported by Mihaylova et al (2005) and our data agree with this, in contrast to the increase reported by Meľuchová et al (2008) or lack of consistent variation reported by Salari et al (2018) for Assaf ewes.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations